Comparative analysis of COVID‐19 case fatality rate between two waves in Nepal. Issue 2 (14th October 2021) - GC, Sulochan; Khanal, Ashok; Paudel, Atmika; GC, Vijay S.; Khanal, Aashis; Panthee, Suresh
Abstract: The first COVID‐19 case in Nepal was reported on January 23, 2020. Then infection, then, started to spread gradually, and October marked the most devastating increase in COVID‐19 cases of the year 2020. Compared with the October 2020 peak in Nepal, the May 2021 peak of COVID‐19 observed 2‐ and 10‐fold rise in new cases and deaths per day, respectively. Given that this surprising increase in the death rate was not observed in other countries, this study analyzed the COVID‐19 case fatality rates between the two peaks in Nepal. We found an increase in death rates among younger adults and people without comorbidities.